Sensitivity of Corynespora cassiicola from barbados cherry to chemical products and field control of target spot (Research, Society and Development, 2022)
The target spot (Corynespora cassiicola), main leaf disease occurred in barbados cherry culture, causing intense defoliation. This study aimed to evaluate the effect of chemical products (fungicides, foliar fertilizers and resistance inducers) on mycelial growth and spore germination of C. cassiicola in vitro and on incidence and severity of target leaf spot in field. The fungitoxic effect of tebuconazol, carbendazin, epoxiconazol + pyraclostrobin, didecyl dimethyl ammonium chloride, Nutriphite P + K and Ecolife® on C. cassiicola in vitro was verified. In field, cabendazin provided lower incidence and severity of target spot, showed satisfactory control of disease.